Regulatory Disharmony of NFTs and the Problematics of Smart Contract Validity: Implications for the Law of Obligations and Fiduciary Security - Anwar, Gamitra; Al-Fatih, Sholahuddin; Arief, Sofyan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
This study analyzes the fundamental regulatory disharmony concerning Non-Fungible Tokens (NFTs) and smart contracts within the Indonesian Civil Law system. The root of the problem is identified as a rechtsvacuüm (legal vacuum) and the